Resilience of sloshing cold fronts against subsequent minor mergers. Issue 1 (30th March 2022) - Vaezzadeh, Iraj; Roediger, Elke; Cashmore, Claire; Hunt, Matthew; ZuHone, John; Forman, William; Jones, Christine; Kraft, Ralph; Nulsen, Paul; Su, Yuanyuan; Churazov, Eugene
ABSTRACT: Minor mergers are common in galaxy clusters. They have the potential to create sloshing cold fronts (SCFs) in the intracluster medium of the cluster. However, the resilience of SCFs to subsequent minor mergers is unknown. Here we investigate the extent to which SCFs established by an off-axis minor merger are disrupted by a subsequent minor merger. We perform a suite of 13 hydrodynamic +  N -body simulations of idealized triple cluster mergers in which we vary the approach direction and impact parameter of the tertiary cluster. Except for ∼1 Gyr after the first core passage of the tertiary cluster, clear SCFs are present in all merger configurations. Subsequent head-on minor mergers reduce the number of SCFs significantly, while subsequent off-axis minor mergers only moderately reduce the number of SCFs. In particular, outer ($\gtrapprox 500\, $ kpc) SCFs are resilient. The results of this work indicate that SCFs are easily formed in the course of a minor merger and are long-lived even if a further minor merger takes place. SCFs thus should be ubiquitous, but deriving the merger history of a given cluster based on its observed SCFs might be more complex than previously thought.